16‐QAM OFDM‐Based W‐Band Polarization‐Division Duplex Communication System with Multi‐gigabit Performance. Issue 2 (1st April 2014) - Kim, Kwang Seon; Kim, Bong‐Su; Kang, Min‐Soo; Byun, Woo‐Jin; Park, Hyung Chul
Abstract : This paper presents a novel 90 GHz band 16‐quadrature amplitude modulation (16‐QAM) orthogonal frequency‐division multiplexing (OFDM) communication system. The system can deliver 6 Gbps through six channels with a bandwidth of 3 GHz. Each channel occupies 500 MHz and delivers 1 Gbps using 16‐QAM OFDM. To implement the system, a low‐noise amplifier and an RF up/down conversion fourth‐harmonically pumped mixer are implemented using a 0.1‐μm gallium arsenide pseudomorphic high‐electron‐mobility transistor process. A polarization‐division duplex architecture is used for full‐duplex communication. In a digital modem, OFDM with 256‐point fast Fourier transform and (255, 239) Reed‐Solomon forward error correction codecs are used. The modem can compensate for a carrier‐frequency offset of up to 50 ppm and a symbol rate offset of up to 1 ppm. Experiment results show that the system can achieve a bit error rate of 10 –5 at a signal‐to‐noise ratio of about 19.8 dB.